Determinants of nostalgia sensitivity in nostalgic driven advertising - Mohammad Hafeez , Bin Mohamad Jowsey; Chong , Chin Wei; Rahman, Muhammad Sabbir (HRMARS, 2015)

(untitled)
The research investigated several determinants potentially influencing consumer sensitivities towards nostalgia sentiment. A total of five variables were selected for investigation, where the research instrument used were survey methods supplemented by a series of nostalgic advertising stimulus; deployed to a sample size of 100 respondents comprising the general Malaysian population. It was revealed that factors such as ageing effect, past childhood experience and event repetition frequency in the past has positive and significant influence over nostalgia sentiment sensitivity of consumers.